A synthetic jasmonate receptor agonist uncouples the growth–defense trade-off in rice - Junli Xiao; Yoko Nakamura; Zhixin Wu; Wenjie Fu; Yumeng Chen; Yonggen Lou; Ian T. Baldwin; Wilhelm Boland; Ran Li (Proceedings of the National Academy of Sciences, 2025)
Herbivore attack elicits jasmonate (JA) signaling which in turn elicits both anti-herbivore plant defenses and growth inhibitions. The resulting growth–defense trade-offs constrain the utility of JA-based plant defense inducers to enhance endogenous pest resistance. Here, we designed and screened selective JA receptor agonists by synthesizing 6-substituted 1-oxoindanoyl isoleucine (In-Ile) conjugates and their free-acid forms, structural mimics of the bioactive hormone (+)-7-iso-jasmonoyl-L-Ile. These compounds differentially activate JA responses through selective binding of specific COI-JAZ coreceptor complexes. Notably, In-Ile treatments enhanced rice resistance to brown planthopper attack, a destructive rice pest, under both laboratory and field conditions, without compromising rice’s growth or yield. Mechanistically, this agonist activates the OsMYB55-mediated lignin biosynthesis defense receptor module [OsCOI1a/2-OsJAZs (3,4,6,7,12)] without activating the growth-suppression receptor module (OsCOI1b-OsJAZs). These findings demonstrate that synthetic JA agonists can provide nuanced manipulations of endogenous plant defenses without yield penalties—a promising biorational strategy for pest control in rice.